A Rare Cause of Abdominal Pain: Giant Omental Lipoma - Kozan, Ramazan; Emral, Ahmet Cihangir; Şahin, Can; Çakmak, Pınar; Aytaç, Abdülkadir Bülent (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Kozan R, Emral AC, Şahin C, Çakmak P, Aytaç AB. A rare cause of abdominal pain: Giant omental lipoma. Turk J Gastroenterol. 2022;33(4):362-364.